Factors related to intention to stop pornography viewing among Malaysian youth facebook users - Lim, Mengzhen (2017)
This is a case study using Ajzen’s Theory of Planned Behaviour (TPB) to understand the intention of Malaysian youths aged between 18 to 30 years old to stop pornography viewing. There were 160 participants who participated in this study via an online survey using purposive sampling method. The minimum age was 18 while the maximum age was 30 with the mean age of 23 years old. In terms of gender distribution, there were 110 males (69%) and 50 females (31%). Majority (61.3%) of the participants was undergraduate students. Attitude toward pornography questionnaire, subjective norms questionnaire, perceived behavioural control questionnaire, religiosity questionnaire were used to assess youth were used to measure independent variables and intention to stop pornography questionnaire was used to measure dependent variable. The reliability of all questionnaires Cronbach's coefficients was administered for all instrument, the result were between 0.72 and 0.94. The results of the study showed that all of the main variables, attitude towards pornography, subjective norms and perceived behavioural control had significant relationship with the intention to stop pornography viewing. Among the three variables, attitude towards pornography was found to be the strongest predictors of intention. Individuals who are committed to religion, who did not masturbate in relation to pornography viewing had higher intention to stop pornography viewing. Theoretically, the present findings underlined the role of attitude toward pornography in influencing the intention to stop pornography among youths in Malaysia. Practically, the finding implies that proper attitude towards pornography play a huge role in stopping pornography viewing.